Supramolecular Chemistry: An Enabling Tool for Asymmetric Catalysis - Cunningham, Laura (Synlett, 2025)
Asymmetric synthesis and supramolecular chemistry are cornerstones of modern organic chemistry. The combination of both fields to develop new approaches to enantioselective catalysis has gained considerable momentum in recent years. Herein, we highlight some of the advantages offered by various supramolecular architectures over conventional chiral catalysts and reflect on obstacles that currently limit widespread use of supramolecular tools in asymmetric synthesis.1 Introduction2 Discussion2.1 Macrocycles2.2 Surfactants2.3 Metal-Organic Cages and Frameworks2.4 Covalent Organic Frameworks2.5 DNA2.6 Mechanically Interlocked Molecules3 Summary and Outlook
Keywords: asymmetric catalysis; supramolecular chemistry; macrocycle; metal-organic assemblies; host–guest systems; mechanically interlocked molecules; micelles